Childhood Maltreatment and Risk of Harm to Self and Others: The Role of Sex and Polyvictimization - Stewart, Shannon L.; Toohey, Ashley; Lapshina, Natalia (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents, 2020)
Objectives: Research has shown that children who experience abuse and neglect are at much higher risk of experiencing negative outcomes such as physical and mental health problems, social skill deficits, and poor quality of life. The goal of this paper was to examine the relationship between polyvictimization and risk of harm to self and others, taking into account both age and sex differences. Methods: A total of 8980 participants (4156 with maltreatment history) were recruited from over 50 mental health facilities in Ontario, Canada. Group comparisons were completed to examine types of trauma experienced, and risk of harm to self and others. Results: Among our sample, we found that 29% of children and youth had experienced multiple types of interpersonal trauma. We also found that while female children and youth who had experienced trauma were at greater risk of harm to themselves, males were at greater risk of harming others. Further, our results highlight that children and youth who had experienced multiple types of maltreatment, regardless of age or sex, were at the greatest risk of harm to self and others. Implications: Findings from this research highlight that interpersonal trauma is multifaceted and add to existing evidence that there is a cumulative relationship between experiencing multiple types of maltreatment and risk in relation to harming oneself or others. Our findings underscore the importance of a background assessment that takes into account all forms of maltreatment in order to properly understand risk of harm and inform intervention.